Allele frequency data for 15 autosomal strs and ancestral proportions using aims-indels in the shuar ethnic group from Ecuador. Issue 1 (December 2019) - Paz-y-Miño, C.; Astudillo-González, O.; Maldonado-Oyervide, D.; López-Cortés, A.; Pérez-Villa, A.; Armendáriz-Castillo, I.; García-Cárdenas, J.M.; Guerrero, S.; Guevara-Ramírez, P.; Yumiceba, V.; Zambrano, A.K.; Leone, P.E.
Abstract: The ethnic group Shuar is located in Ecuador. To identify their genetic composition, 46 ancestry-informative insertion deletion markers (AIM-INDELs) were used. Also, characterization of 15 tandem repeats (STRs) in the AmpFISTR Identifiler Kit were applied. Forensic parameters showed a matching probability of 0.1535, a power of discrimination of 0.8465, a polymorphism information content of 0.6584, probability of exclusion of 0.415 and a typical paternity index of 1.78. The Shuar are not influenced by admixture population events, being a Native American group 98.7%, along with a genetic diversity of 0.699346+/-0.356964.